Challenges of Professionalization in Gerontology - Melo, Ruth Caldeira de (2015)
The professionalization of gerontologist, professional with a generalist background that is able to integrate biopsychosocial knowledge in the management of old age and aging, is a difficult task that should be embraced by all involved in his/her academic formation. This paper aims to present a reflection on the trajectory of the professionalization of Bachelor in Gerontology in Brazil and other countries, raising the main challenges and possible strategies for its recognition as a profession.